Drainage Network System of UTHM Campus - AHMAD ISKANDIR, NURDIANA; WAI TAN, Lai (Recent Trends in Civil Engineering and Built Environment, 2022)
Rapid development has led to many physical changes in Malaysia, such as drainage system, including at Universiti Tun Hussein Onn Malaysia campus. The development also speeds up the deterioration of living conditions, such as wastewater blockage, wastewater sedimentation, and stream pollution during the rainy season. The study aims to produce drainage network system that compiles drainage characteristics of Universiti Tun Hussein Onn Malaysia. The study area covers approximately 500,000 m² of the campus. Characteristics of drainage recorded are cross-section, longitudinal slope and Manning’s roughness coefficient. Roughness coefficient is obtained from Manning’s roughness flow equation. Equipment used is measuring tape, wheeling meter, float and stopwatch to get dimension and longitudinal slope of the drain, and velocity of flow. All drains are observed to be rectangular and trapezoidal sections. Bottom width and longitudinal slope of the drains range from 0.1 m to 4.0 m and 0.0005 to 0.0805, respectively. Depths of flow in the drains are found to be between 0.02 m and 1.05 m. Meanwhile, the average velocity of flow is between 0.017 m/s and 0.1603 m/s. Compilation of UTHM campus drainage network system provides information for better management of the drainage system.